Pengaruh model flipped classroom berbantuan edpuzzle terhadap hasil belajar IPAS siswa kelas 5 SDN 13 Palembang - Siti Marlina; Kiki Aryaningrum; Adrianus Dedy (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study aims to determine whether the use of the flipped classroom model assisted by edpuzzle can improve the learning outcomes of students in class V of SDN 13 Palembang. This study is a type of quantitative research using an experimental method of True Experimental Design research in the form of Posttest-only Control Design. The variables of this study consist of independent variables (X), namely the flipped classroom model assisted by edpuzzle and dependent variables (Y), namely the learning outcomes of science. The population of this study were all students in class V of SDN 13 Palembang. Sampling from this study used the Probability Sampling technique, namely Simple Random Sampling where the samples were classes VC and VD totaling 51 students. Data collection techniques used tests and documentation. Validation of the test instrument was tested using the Product Moment correlation formula and the reliability test used Alpha Cronbach. The data analysis technique used the Independent Samples T-Test which was carried out after the normality and homogeneity tests were known. The experimental class that was given treatment using the flipped classroom model assisted by edpuzzle obtained an average posttest of 80.43 and the control class obtained an average of 60.00. The results of the T-Test with t_table 1.677 obtained t_(count) of 5.389, it can be concluded that there is a significant influence of the use of the flipped classroom model assisted by edpuzzle on the science learning outcomes of grade 5 students of SDN 13 Palembang